2013
DOI: 10.1038/ncomms3443
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BIG3–PHB2 interaction to overcome tamoxifen resistance in breast cancer cells

Abstract: The acquisition of endocrine resistance is a common obstacle in endocrine therapy of patients with oestrogen receptor-α (ERα)-positive breast tumours. We previously demonstrated that the BIG3–PHB2 complex has a crucial role in the modulation of oestrogen/ERα signalling in breast cancer cells. Here we report a cell-permeable peptide inhibitor, called ERAP, that regulates multiple ERα-signalling pathways associated with tamoxifen resistance in breast cancer cells by inhibiting the interaction between BIG3 and PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(135 citation statements)
references
References 51 publications
5
130
0
Order By: Relevance
“…Previous studies have shown that BIG3 is frequently upregulated in ERα-positive breast cancers56 and here we found that the overexpression of BIG3 was significantly correlated with the poorer prognosis of patients with ERα-positive breast cancer based on the RNAseq2 data set from the Cancer Genome Atlas (Supplementary Fig. 5a, Log rank test; P <0.001).…”
Section: Resultssupporting
confidence: 64%
“…Previous studies have shown that BIG3 is frequently upregulated in ERα-positive breast cancers56 and here we found that the overexpression of BIG3 was significantly correlated with the poorer prognosis of patients with ERα-positive breast cancer based on the RNAseq2 data set from the Cancer Genome Atlas (Supplementary Fig. 5a, Log rank test; P <0.001).…”
Section: Resultssupporting
confidence: 64%
“…PHB2 is a tumor suppressor that on activation has been shown to prevent the progression of ERα positive breast cancer [72]. Because of its anti-estrogenic effects, it abrogates the signaling of nuclear as well as membrane associated ERα [73]. These data indicate that flaxseed is effective in altering the expression of genes implicated in a number of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-based assays and mouse xenograft studies showed that ERAP completely suppressed E2-dependent breast cancer cell growth in vitro and in vivo , respectively 10 . However, its inhibitory effect was only maintained for 24 h, most likely due to its high susceptibility to proteolytic degradation.…”
Section: Introductionmentioning
confidence: 99%